Anatomy and Function of Ventral Tegmental Area Glutamate Neurons - Cai, Jing; Tong, Qingchun (Frontiers in Neural Circuits, 2022)
The ventral tegmental area (VTA) is well known for regulating reward consumption, learning, memory, and addiction behaviors through mediating dopamine (DA) release in downstream regions. Other than DA neurons, the VTA is known to be heterogeneous and contains other types of neurons, including glutamatergic neurons. In contrast to the well-studied and established functions of DA neurons, the role of VTA glutamatergic neurons is understudied, presumably due to their relatively small quantity and lack of effective means to study them. Yet, emerging studies have begun to reveal the importance of glutamate release from VTA neurons in regulating behaviors and drug addictions through a complex intra-VTA and long-range neuronal network. In this review, we summarize the features of VTA glutamatergic neurons from three perspectives: cellular properties, neural connections, and behavioral functions. Delineation of VTA glutamatergic pathways and their interactions with VTA DA neurons in regulating behaviors may lead to previously unappreciated functions of the VTA in other physiological processes.